Flow injection analysis of 5-(hydroxymethyl)-2-furaldehyde in honey by a modified winkler method - Castoldi, Karine [UNESP]; Milani, Maria Izabel [UNESP]; Rossini, Eduardo L. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena R. [UNESP] (Springer Nature, 2016)
One of the quality indicators for honey is 5-(hydroxymethyl)-2-furaldehyde (HMF), which is formed during the heating or aging of honey. The International Honey Commission recommends three methods for the determination of HMF in honey: the Winkler method, the White method, and determination by HPLC. The Winkler method uses the carcinogenic substance p-toluidine, which is not in accordance with the principles of Green Chemistry. The present work describes the determination of HMF in honey by flow injection analysis (FIA) using a modified Winkler method, replacing p-toluidine with p-aminobenzoic acid. The linear range was 1.00 to 40.0 mg L-1, the limit of detection (LOD) was 0.43 mg L-1, and the limit of quantification (LOQ) was 1.32 mg L-1. The method is an efficient and environmentally friendly technique for the analysis of HMF in honey.
Keywords: 5-(hydroxymethyl)-2-furaldehyde (HMF); Flow injection analysis; Honey; P-aminobenzoic acid